(untitled) (Research, Society and Development, 2021)
The objective of this research was to test the effect of Hydropriming to promote the emergence and vigor in seeds of members of the Caatinga biome. Therefore, the following species were tested: Sesbania virgata, Anadenanthera colubrina, Luetzelburgia auriculata, Cenostigma pyramidale, Vachelia farnesiana, Piptadenia retusa, Senna spectabilis, Mimosa tenuiflora, Sarcomphalus joazeiro and Enterolobium contortisiliquum. There were two treatments: 1) immersion in water (Hydrocondditioning) for 24h at 25 ° C and 2) incubation for 24h at 25 ° C without immersion. Emergence and vigor variables were assessed. The results obtained were tested by Chi-square and non-parametric tests. Hydropiming technology was not advantageous for species studied in this research, except for Anadenanthera colubrina and Luetzelburgia auriculata. Therefore, a 24h immersion at 25 ° C is potential to promote the emergence and vigor of Anadenanthera colubrina and Luetzelburgia auriculata, further research can be carried out to improve the management of these species.